PENGEMBANGAN MODEL KOMUNIKASI EDUKATIF REINVENTING SUBSCONCIOUS MIND (RESMI) UNTUK MADRASAH IBTIDAIYAH - Prastowo, Andi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The effort to develop communicative competence of Madrasah Ibtidaiyah teachers in Indonesia is still low. It is shown from various upgrading programs for teacher’s professionalism and quality which rarely touch communicative competence aspect. However, government regulation on academic qualification standard and teacher competence stated that communicative competence becomes the bases of pedagogic, social, and professional competences, except personality competence. In addition, in teacher training institute the course on learning communication is not always given. While communication play an important role for effective learning process. This article presents the research of development of Fikih learning communications model in Madrasah Ibtidaiyah namely reinventing subconscious mind (RESMI). The result shows that its implementation improves the familiarity between teachers and pupils, learning enthusiasm, ability to memorize materials, and improve learning achievement.